The FGF8-related signals Pyramus and Thisbe promote pathfinding, substrate adhesion, and survival of migrating longitudinal gut muscle founder cells. - Reim, I.; Hollfelder, D.; Ismat, A.; Frasch, M. (Developmental Biology, 2012)
Fibroblast growth factors (FGFs) frequently fulfill prominent roles in the regulation of cell migration in various contexts. In Drosophila, the FGF8-like ligands Pyramus (Pyr) and Thisbe (Ths), which signal through their receptor Heartless (Htl), are known to regulate early mesodermal cell migration after gastrulation as well as glial cell migration during eye development. Herein, we show that Pyr and Ths also exert key roles during the long-distance migration of a specific sub-population of mesodermal cells that migrate from the caudal visceral mesoderm within stereotypic bilateral paths along the trunk visceral mesoderm toward the anterior. These cells constitute the founder myoblasts of the longitudinal midgut muscles. In a forward genetic screen for regulators of this morphogenetic process we identified loss of function alleles for pyr. We show that pyr and ths are expressed along the paths of migration in the trunk visceral mesoderm and endoderm and act largely redundantly to help guide the founder myoblasts reliably onto and along their substrate of migration. Ectopically-provided Pyr and Ths signals can efficiently re-rout the migrating cells, both in the presence and absence of endogenous signals. Our data indicate that the guidance functions of these FGFs must act in concert with other important attractive or adhesive activities of the trunk visceral mesoderm. Apart from their guidance functions, the Pyr and Ths signals play an obligatory role for the survival of the migrating cells. Without these signals, essentially all of these cells enter cell death and detach from the migration substrate during early migration. We present experiments that allowed us to dissect the roles of these FGFs as guidance cues versus trophic activities during the migration of the longitudinal visceral muscle founders.